ANALYSIS OF STUDENTS’ READING HABIT TOWARDS ACADEMIC TEXT - Maghfirotin Hardianti Rizqy (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Reading material in this era of technology can be accessed easily through internet which offer access to information especially for newer generations. The availability of digital reading material in the internet allows the reader to access all kinds of information from around the world, it means that every individual in this world with internet coverage have the same opportunity to gain knowledge. For this reason, the researcher interested in conducting study about the students reading habit in digital setting. This study was implemented using descriptive qualitative method though online questionnaire and semi-structured interviews. The data for this research were collected from 10 students of the English department from the 7th Semester at University of Islam Malang. The data are analyzed using qualitative analysis that consists of data reduction, grouping, coding, and interpretation to get the data as a conclusion. The results show that the students' reading frequency is mostly determined by academic demands and necessity. All the students also preferred digital text due to its practicality, easy to use and availability of the material on the internet, and the students tend to choose lightweight and shorter reading materials. All the students give positive responses due to the convenience and familiarity of using digital text as well as experience in reading digital academic text. However, there are also difficulties encountered by students like visual problems, eyestrain, tiredness and technical issues like taking too long to open, corrupted file, the gap between lecturer and students in reading method and protection in some downloaded digital text.Key Words: Digital reading, habit, English.